A tutela da posse dos imóveis públicos - Santos, Rodrigo Ferreira (2013)
The ownership of public property is the subject that, although of great importance, has not been parsed with the necessary care by doctrine and national courts. This study start of an essential distinction between the various kinds of public buildings, that guides the analysis of possession and its consequences. Possession will exist whenever there is factual power over good, provided there is no pre delete warning clause of jurisdicidade. In a second step, evaluates the effectiveness of ownership over that property public, taking into account the characteristics of the possession and the subjects involved. Existing ownership, its consequences (legal effect) will vary according to the class to which that public good fits and this condition will affect the judicial protection of ownership. You can't conceive a wayward material law possessory supervision that governs the situation being addressed. In the case of dominicias, it is possible a full guardianship of private ownership, which inexistirá in the case of goods of special use.